The cost of music. Issue 1 (February 2020) - Brennan, Matt; Devine, Kyle
Abstract: What is the cost of music in the so-called Anthropocene? We approach this question by focusing on the case of sound-recording formats. We consider the cost of recorded music through two overlapping lenses: economic cost, on the one hand, and environmental cost, on the other. The article begins by discussing how the price of records has changed from the late 19th to the 21st century and across the seven most economically significant playback formats: phonograph cylinder, gramophone disc, vinyl LP, cassette tape, compact disc, digital audio files on hard drive, and streaming from the cloud. Our case study territory is the United States, and we chart the gradual decline in the price of recorded music up to the present. We then examine the environmental and human costs of music by looking at what recordings are made out of, where those materials come from, and what happens to them when they are disposed of. Despite what rhetorics of digital dematerialisation tell us, we show that the labour conditions in the digital electronics and IT industries are as inhumane as ever, while the amount of greenhouse gases released by the US recording industry could actually be higher today than at the height of any previous format. We conclude by asking the obvious (but by no means straightforward) question: what are musicians and fans to do?